CD133 Expression and Identification of CD133/nestin Positive Cells in Rhabdomyosarcomas and Rhabdomyosarcoma Cell Lines. (2011) - Sana, Jiri; Zambo, Iva; Skoda, Jan; Neradil, Jakub; Chlapek, Petr; Hermanova, Marketa; Mudry, Peter; Vasikova, Alzbeta; Zitterbart, Karel; Hampl, Ales; Sterba, Jaroslav; Veselska, Renata
Abstract : Background : Co-expression of CD133, cell surface glycoprotein, and nestin, an intermediate filament protein, was determined to be a marker of neural stem cells and of cancer stem cells in neurogenic tumors. Methods : We examined the expression of CD133 and nestin in ten tumor tissue samples taken from patients with rhabdomyosarcomas and in five rhabdomyosarcoma cell lines. Immunohistochemistry and immunofluorescence were used to examine FFPE tumor tissue samples. Cell lines were analyzed by immunofluorescence, immunoblotting, flow cytometry, and RT-PCR. Functional assays (clonogenic in vitro assay and tumorigenic in vivo assay) were also performed using these cell lines. Results : CD133 and nestin were detected in all 10 tumor tissue samples and in all 5 cell lines; however, the frequency of CD133+, Nes+, and CD133+/Nes+ cells, as well as the intensity of fluorescence varied in individual samples or cell lines. The expression of CD133 and nestin was subsequently confirmed in all cell lines by immunoblotting. Furthermore, we observed an increasing expression of CD133 in relation to the cultivation. All cell lines were positive for Oct3/4 and nucleostemin; NSTS-11 cells were also able to form xenograft tumors in mice. Conclusion : Our results represent the first evidence of CD133 expression in rhabdomyosarcoma tissue and in rhabdomyosarcoma cell lines. In addition, the co-expression of CD133 and nestin as well as results of the functional assays suggest a possible presence of cancer cells with a stem-like phenotype in these tumors.